Biologic use in hidradenitis suppurativa: patient perspectives and barriers. (3rd October 2022) - De, Devea R.; Shih, Terri; Fixsen, Denise; Brooks, Brindley; Hsiao, Jennifer L.; Shi, Vivian Y.
Abstract: Introduction: Hidradenitis suppurativa (HS) is an inflammatory dermatosis for which the treatment paradigm is rapidly expanding. We aimed to identify HS patient perspectives and barriers on biologics. Methods: An anonymous survey was distributed between 10/2021 and 1/2022 through HS support groups. Data regarding demographics and perspectives on biologics were collected and analyzed. Results: Of the 196 respondents, 92% were female (180/196) and 75% were white (147/196). 89.3% had Hurley stage 2/3 HS (102/195). The primary healthcare provider (HCP) for HS in 65% (128/196) of patients was a dermatologist, with 12% (23/196) seen at an HS specialty clinic. Most respondents never tried a biologic medicine (62%, 118/192). The top barriers to biologics were fear of side effects (61%, 109/179), high cost/lack of insurance coverage (46%, 83/179), frequency of weekly injections (32%, 58/179). Respondents reporting their main HCP as a non-dermatologist (4.11 vs 3.0, p  < .0001) and not seen at a HS specialty clinic (3.5 vs 2.7, 0.039) were significantly more likely to agree 'I do not know enough about how biologics work to help my HS'. Conclusion: Our results highlight the importance of specialty care in the education and implementation of biologics. Patients may benefit from comprehensive discussion prior to starting biologics.